Study on Hydrolysis-Acidification-A2O Sludge Reduction Process for Operation Performance - Zuo, Ning; Ji, Fang-Ying (Asian Journal of Chemistry, 2012)
An advanced process combining sludge reduction and phosphorous and nitrogen removal is developed, for short hydrolysis-acidogenosis-anaerobic/anoxic-multistep continuous oxic tank [HA-A/A-MCO] process, whose biological treatment unit is hydrolysis-acidification, multistep continuous oxic tank and continuous flow A2/O process coupled with side stream phosphorous removal by draining out anaerobic phosphorous accumulating sewage. Test results of the process treating campus wastewater show that under the condition of SRT = 60d, the influent COD = 316 to 407 mg/L, NH3-N = 30 to 40 mg/L, TN = 35 to 53 mg/L, TP = 6 to 9 mg/L, the effluent COD, NH3-N, TN and TP are equal to or less than 18 mg/L, 2.1 mg/L, 10.3 mg/L, 0.44 mg/L, respectively. VFA from hydrolysis-acidification process can improve phosphorous and nitrogen removal effectively, which can induce phosphorous content from anaerobic release reaching 57 mg/L and can make the amount of sidestream phosphorous removal sewage flowing into chemical phosphorous removal tank be just 13 % of influent flow. Nitrogen removal is realized by simultaneous nitrification and denitrification (SND) and only denitrification, which account for 50 % and 26 % of the total nitrogen removal respectively. Moreover, biofacies separation is realized in HA-A/A-MCO process and lower sludge yield which is 0.1 gMLSS/gCOD can be achieved by utilizing biological predation.